Charge-sensitive front-end electronics with operational amplifiers for CdZnTe detectors. (2nd September 2016) - Födisch, P.; Berthel, M.; Lange, B.; Kirschke, T.; Enghardt, W.; Kaever, P.
Abstract: Cadmium zinc telluride (CdZnTe, CZT) radiation detectors are suitable for a variety of applications, due to their high spatial resolution and spectroscopic energy performance at room temperature. However, state-of-the-art detector systems require high-performance readout electronics. Though an application-specific integrated circuit (ASIC) is an adequate solution for the readout, requirements of high dynamic range and high throughput are not available in any commercial circuit. Consequently, the present study develops the analog front-end electronics with operational amplifiers for an 8×8 pixelated CZT detector. For this purpose, we modeled an electrical equivalent circuit of the CZT detector with the associated charge-sensitive amplifier (CSA). Based on a detailed network analysis, the circuit design is completed by numerical values for various features such as ballistic deficit, charge-to-voltage gain, rise time, and noise level. A verification of the performance is carried out by synthetic detector signals and a pixel detector. The experimental results with the pixel detector assembly and a 22 Na radioactive source emphasize the depth dependence of the measured energy. After pulse processing with depth correction based on the fit of the weighting potential, the energy resolution is 2.2% (FWHM) for the 511 keV photopeak.